Inovasi Resep Lumpia Goreng Isi Jantung Pisang untuk Meningkatkan Daya Saing dalam Industri Kuliner - Elis Rumni; Fitri Ardiyani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Semarang spring rolls are generally filled with bamboo shoots, which some people may not prefer. In this study, banana flower was chosen as an alternative filling, considering its potential for processing, particularly in sambal. The aim of this research is to evaluate the level of preference among panelists for fried spring rolls filled with banana flower based on five attributes: appearance, color, texture, aroma, and taste, as well as to determine a standard recipe, business analysis, and product shelf life. The method used is research and development with a hedonic test involving 20 panelists, including 5 expert panelists and 15 trained panelists. The results indicate a very positive level of preference: appearance (80%), color (95%), texture (95%), aroma (85%), and taste (90%). The standard recipe consists of 250 grams of banana heart, 15 grams of dried shrimp, 1 egg, and other ingredients, yielding 16 pieces per batch. The business analysis shows a cost price of IDR 6,190 per pack (containing 5 pieces), with a break-even point of 165 packs per day and a profit target of IDR 5,000,000 with sales of 753 packs per month. The shelf life of the spring rolls at chiller temperature (4ºC–6ºC) is proven to last up to 5 days before frying. This study recommends further development in the processing techniques of banana heart to improve its digestibility.